Elastic analysis of thin fiber-reinforced plates = Analiza sprężystych płyt zbrojonych włóknami - Kuczma, Mieczysław; Kula, Krzysztof (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper is concerned with the bending problem of a fibre-composite plate in the elastic range. Within the classical Kirchhoff plate theory, two approaches are utilized. In the model due to Świtka, the fibre-composite plate is treated as a homogeneous medium with a number of embedded families of fibres, while in the second model the plate is considered as a system of orthotropic layers. The bending problem is formulated in classical and variational forms and solved by finite element method. We have developed our own computer code and numerically compared predictions of the two models and other models available in the program ABAQUS on test examples. Numerical results illustrating influence of the placement of fibres on the quantities of interest are also included.
Keywords: sprężyste płyty zbrojone; płyty włóknokompozytowe; model Świtki; metoda elementów skończonych; fibre-composite layered plate; bending of anisotropic plate; Finite Element Method (FEM); elastic solution